Experimental Study on Thermal Insulation Effect of the Buried Oil-Gas Pipelines in Permafrost Regions - Deren Liu; Jiale Yang; Xu Wang; Junming Zhao; Shuochang Xu; Yongchun Zhao (Geofluids)
In permafrost regions, long distance buried pipelines are widely used to transport oil and natural gas resources. However, pipeline problems occur frequently due to the complicated surrounding environment and transportation requirement of positive temperature. In this study, a thermal insulation layer was applied to mitigate permafrost degeneration around the buried oil-gas pipelines. Based on engineering background of the Sebei-Xining-Lanzhou natural gas pipeline in China, an indoor model test was designed and carried out in which many key indices, such as the temperature regime, vertical displacement, pipeline wall stress, and water content, were closely monitored. The test results indicate that the large heat loss of the buried pipeline produces a rapid increase in ground temperatures which seriously reduces the bearing capacity of the permafrost foundation. The buried oil-gas pipelines with a thermal insulation layer can effectively reduce the thawing range and vertical displacement of the permafrost foundation around the buried pipelines, so as to control the stress of the pipeline wall in the normal range and protect the safe and stable operation of the buried oil-gas pipelines. The experimental results can serve as a reference for the construction, operation, and maintenance of buried oil-gas pipelines in permafrost regions.